Strategic Planning in Education: Preventing Suicide through Peer Counseling and Mental Health Detection - Yudistira, Satria (Jurnal Educatio FKIP UNMA, 2025)
This study explores the effectiveness of peer counseling programs in detecting mental health issues among students, with a focus on the role of educational leadership in promoting early detection and the development of relevant strategies for program implementation in Indonesia. Using a mixed-methods approach, the research combines qualitative data from interviews and observations with quantitative analysis to assess the impact of peer counseling on students' mental well-being. The findings highlight the positive effects of peer counseling on students’ emotional support, although challenges such as stigma, lack of supervision, and limited resources were also identified. The study emphasizes the need for strong leadership, tailored strategies, and the integration of technology to ensure the sustainability and effectiveness of peer counseling programs in Indonesian schools.